A 2-Dof LQR based PID controller for integrating processes considering robustness/performance tradeoff. (November 2017) - Srivastava, Saurabh; Pandit, V.S.
Abstract: This paper focuses on the analytical design of a Proportional Integral and Derivative (PID) controller together with a unique set point filter that makes the overall Two-Degree of-Freedom (2-Dof) control system for integrating processes with time delay. The PID controller tuning is based on the Linear Quadratic Regulator (LQR) using dominant pole placement approach to obtain good regulatory response. The set point filter is designed with the calculated PID parameters and using a single filter time constant ( λ ) to precisely control the servo response. The effectiveness of the proposed methodology is demonstrated through a series of illustrative examples using real industrial integrated process models. The whole range of PID parameters is obtained for each case in a tradeoff between the robustness of the closed loop system measured in terms of Maximum Sensitivity (Ms ) and the load disturbance measured in terms of Integral of Absolute Errors (IAE). Results show improved closed loop response in terms of regulatory and servo responses with less control efforts when compared with the latest PID tuning methods of integrating systems. Highlights: Analytical 2-Dof LQR-PID controller is designed for integrating systems with time delay. More flexibility to choose PID parameters considering performance/robustness tradeoff. Better load regulation is achieved with improved sensitivity. Set point filter is uniquely designed using LQR-PID and single tuning parameter λ . Set point filter precisely controls the overshoot and reduces initial control effort.